Phosphorylation of meprin β controls its cell surface abundance and subsequently diminishes ectodomain shedding. Issue 7 (14th June 2021) - Armbrust, Fred; Bickenbach, Kira; Koudelka, Tomas; Tholey, Andreas; Pietrzik, Claus; Becker‐Pauly, Christoph
Abstract: Meprin  β is a zinc ‐dependent metalloprotease exhibiting a unique cleavage specificity with strong preference for acidic amino acids at the cleavage site. Proteomic studies revealed a diverse substrate pool of meprin β including the interleukin‐6 receptor (IL‐6R) and the amyloid precursor protein (APP). Dysregulation of meprin β is often associated with pathological conditions such as chronic inflammation, fibrosis, or Alzheimer's disease (AD). The extracellular regulation of meprin β including interactors, sheddases, and activators has been intensively investigated while intracellular regulation has been barely addressed in the literature. This study aimed to analyze C‐terminal phosphorylation of meprin β with regard to cell surface expression and proteolytic activity. By immunoprecipitation of endogenous meprin β from the colon cancer cell line Colo320 and subsequent LC‐MS analysis, we identified several phosphorylation sites in its C‐terminal region. Here, T694 in the C‐terminus of meprin β was the most preferred residue after phorbol 12‐myristate 13‐acetate (PMA) stimulation. We further demonstrated the role of protein kinase C (PKC) isoforms for meprin β phosphorylation and identified the involvement of PKC‐α and PKC‐β. As a result of phosphorylation, the meprin β activity at the cell surface is reduced and, consequently, the extent of substrate cleavage is diminished. Our data indicate that this decrease of the surface activity is caused by the internalization and degradation of meprin β.